Low-cost and eco-friendly synthesis of silver nanoparticles using coconut (Cocos nucifera) oil cake extract and its antibacterial activity. (16th November 2016) - Govarthanan, Muthusamy; Seo, Young-Seok; Lee, Kui-Jae; Jung, Ik-Boo; Ju, Ho-Jong; Kim, Jae Su; Cho, Min; Kamala-Kannan, Seralathan; Oh, Byung-Taek
Abstract: The present study reports the simple, inexpensive, eco-friendly synthesis of silver nanoparticles (AgNPs) using coconut oil cake extract. Scanning electron microscopy–energy dispersive spectroscopy peak at 3 keV confirmed the presence of silver. Transmission electron micrograph showed that nanoparticles are mostly circular with an average size of 10–70 nm. The results of the X-ray powder diffraction analysis (2 θ  = 46.2, 67.4 and 76.8) indicated the crystal nature of the AgNPs. Fourier transform infrared spectroscopy analysis indicates that proteins present in the oilcake extract could be responsible for the reduction of silver ions. The synthesized AgNPs (1–4 mm) reduced the growth rate of multi-antibiotic-resistant bacteria such as Aeromonas sp., Acinetobacter sp. and Citrobacter sp. isolated from livestock wastewater.